2) Ejercicios combinados:
Resultados
3.
2
6
a)
+
II
31
a)
3 14
35
4
99
3
b)
80
13
c)
60
b) · (2+3)
c) - 6+2-3) =
d) 5+ - 13): 3 =
e) -: 06:+)-(-5) =
f) [(3+3)-3-(2+3:3) - =
g) {[(4 +-2):11 +1 3:6
11
e) -
12
+
4.
6 =
6=
3)
15
Respuestas a la pregunta
Contestado por
1
Respuesta:
tenes q multiplicar la operación cuando el resultado esta mal
Otras preguntas
Matemáticas,
hace 4 meses
Informática,
hace 4 meses
Ciencias Sociales,
hace 4 meses
Filosofía,
hace 8 meses
Matemáticas,
hace 8 meses
Filosofía,
hace 1 año
Ciencias Sociales,
hace 1 año
Matemáticas,
hace 1 año